Assessment of 10-year fracture risks in postmenopausal women by the FRAX™ algorithm, standardised for Italian, Spanish and UK populations - Skowrońska-Jóźwiak, Elżbieta; Wójcicka, Agata; Lorenc, Roman S.; Lewiński, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Taking into consideration the growing incidence of osteoporotic fractures, identification of patients with the highest fracture risk seems to be the most rational and cost-effective solution of this clinical problem. The fracture risk assessment tool (FRAX) is a new diagnostic method, proposed by the World Health Organization and designed for 10-year fracture risk evaluation; there is no Polish version of the FRAX calculator yet. Objectives: Assessment of 10-year fracture risk scores in postmenopausal women of the Lodz population, based on the FRAX algorithm, standardised for the populations of Italy, Spain and the UK. Material and methods: The study group included 94 postmenopausal females (55-80), divided into five age subgroups. The patients completed a questionnaire form, designed to analyze osteoporosis risk factors, and were then submitted to femoral neck densitometry by a DXA (dual energy X-ray absorptiometry) scanner (Lunar EXPERT). The 10-year fracture risk was assessed by the FRAX method, using a calculator standardised for the populations of Italy, Spain and the UK. FRAX major (the risk of main osteoporotic fractures) and FRAX hip (the risk of femoral neck fractures) were calculated, using obtained densitometric results (FMD, FHD) and BMI (FM, FH). Results: In each age subgroup, the highest scores of 10-year fracture risk (FRAX major, FRAX hip) were obtained, using the UK-oriented calculator, while the lowest ones were found applying the calculator standardised for Spain. The differences were statistically significant and affected patient qualification for therapy vs. established intervention threshold. Conclusions: 1. The outcome supports the need for a Polish FRAX calculator with a properly adapted intervention threshold. 2. It is fairly justified to use the British calculator option until the Polish FRAX version is available.